Redescription of the Skull of Coloradisaurus brevis (Dinosauria, Sauropodomorpha) from the Late Triassic Los Colorados Formation of the Ischigualasto-Villa Union Basin, northwestern Argentina - Apaldetti, Graciela Cecilia (2014)
The cranial anatomy of the basal sauropodomorph Coloradisaurus brevis from the upper levels of the Norian Los Colorados Formation is here redescribed and comparisons made based on the holotype skull and mandible. Coloradisaurus brevis is diagnosed by most of the features proposed in the original description and an additional set of autapomorphies, such as presence of circular upper temporal fenestrae, laminae on the ventrolateral margins of a ventral fossa of the basisphenoid and on the ventral region of the parasphenoid, and tab-like medial process at the posteromedial end of the mandible. Coloradisaurus is placed within Massospondylidae, as in recent analyses. This position is supported primarily by postcranial characters, but some cranial features identified in this study provide additional evidence supporting this position (e.g., jugal contribution to the antorbital fenestra, frontal proportionately longer than nasals). However, the cranial anatomy of Coloradisaurus also bears several characters that are shared with plateosaurids (e.g., low mandibular articulation, broad maxillary wall on the anterior margin of antorbital fossa, broad prefrontals, projection of infratemporal fenestra behind the orbit, stepped braincase, robust septum between basipterygoid processes). Thus, Coloradisaurus is interpreted as a massospondylid that has convergently acquired characters that are otherwise only known in plateosaurids, highlighting the conflicting pattern of character distribution among basal sauropodomorphs.